The fourth estate’s invisible hand: how newspaper media legitimize neoliberal higher education in Qatar and the UAE - Sellami, Abdellatif; Abu-Tineh, Abdullah Mohammad Hamdan; Alshaboul, Yousef Mohammad Khaled; Ghamrawi, Norma Abdulrahman; Shal, Tarek Mustapha (Frontiers in Education, 2025)
This study critically examines how English-language newspaper discourse in Qatar and the UAE constructs and legitimizes neoliberal ideologies surrounding higher education institutions and international branch campuses. Drawing on critical theory and critical discourse analysis, we delve into the discourses used in newspaper articles published between 2010 and 2024. We explore the underlying meanings, ideologies, and power relations embedded in the discourses that present institutions of higher education as providers of world-class education and models of best practices. Our findings reveal common themes shared across the two countries, emphasizing commitment to excellence, global leadership, world-class education, and best practices. At the same time, distinctions unique to each are identified, suggesting different approaches to holistic development, diversity, inclusivity, and the importance attributed to international recognition and rankings. This study enriches our understanding of the way neoliberal ideologies permeate discourses, influencing and being influenced by the academic landscape, thus charting new paths for future directions in this area.